2015
DOI: 10.2500/aap.2015.36.3834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of systemic corticosteroids on serum apoptotic markers and quality of life in patients with asthma

Abstract: Despite corticosteroids being the first line drug treatment for asthma symptom control, the mechanisms of action of corticosteroids in asthma are still poorly understood. The current study aimed to evaluate the effect of systemic corticosteroids on serum level of apoptotic markers Survivin (for inflammatory cells) and M30 apoptosense (for bronchial epithelial cells) in patients of acute exacerbation of bronchial asthma. The study involved 60 patients with acute exacerbation of bronchial asthma who were prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Systemic corticosteroids seem to significantly improve quality of life [ 22 ], however, only seven of our patients received systemic corticosteroids and although on average their QoL was higher, this difference was statistically not significant. Schatz et al [ 7 ] reported asthma-specific QoL during pregnancy is related to asthma exacerbations and to perinatal outcomes.…”
Section: Discussionmentioning
confidence: 88%
“…Systemic corticosteroids seem to significantly improve quality of life [ 22 ], however, only seven of our patients received systemic corticosteroids and although on average their QoL was higher, this difference was statistically not significant. Schatz et al [ 7 ] reported asthma-specific QoL during pregnancy is related to asthma exacerbations and to perinatal outcomes.…”
Section: Discussionmentioning
confidence: 88%
“…These comorbidities are also linked with the use of drugs that were identified in our study as putative risks like amlodipine and methylprednisolone. Researchers had already proved that the use of both, calcium channel blockers and corticosteroids in the treatment of chronic disease, in fact, increased patients' quality of life [35][36][37] . Therefore, it seems that the quality of life in the mechanically ventilated CAP patients is influenced rather by the complex milieu of numerous subtleacting, highly interconnected, intrinsic and acquired factors than by the profound effects of leading causes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Bhargava et al (2015) evaluated the effect of systemic corticosteroids on a new serum apoptotic markers, Survivin and M30 apoptosense in asthmatic patients. The study was conducted in 60 patients with acute exacerbation of bronchial asthma and treated with systemic corticosteroids.…”
Section: Newer Biomarkers In Respiratory Disordersmentioning
confidence: 99%